Impacts of Gadget on Early Childhood Development: How to Solve the Addiction Gadget? - Rissa Wahyuningtyas; Rochanah Rochanah; Toyirova Shahlo Izatovna (Bulletin of Early Childhood, 2022)
Gadget were the most frequently used daily communication tools. Gadgets have been used by many people, not only adults but also young people. This article desribed using gadget either positive or negative impact on early childhood development and giving solution in addiction gadget of childhood development. The researchers used qualitative method. The collecting data used interview and documentation. There was 10 participants in this interview. The documentation collecting by reviewing some of the previous findings with a coding system and in-depth analysis of each data. The researchers conducted an online search on Google Schoolar, Science Direct, et all, specifically on articles published between 2010 to 2022. The result showed that Gadgets have a bad impact on children, for instance decreased concentration power, weak emotional control, and health problems. The right communication model from parents can decrease children addiction.